1996
DOI: 10.1107/s0108767396003960
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic X-ray Elastic Scattering Factors for He–Ar from Dirac–Hartree–Fock Wave Functions

Abstract: X-ray and electron elastic scattering factors for He through Ar ground states have been computed from Dirac-Hartree-Fock (DHF) wave functions. Differing from earlier studies, the present DHF wave functions are not restricted to single configurations and will go into the nonrelativistic Hartree-Fock (HF) ground states when the speed of light c --, ~. The relativistic effects have been analyzed through the differences of scattering factors calculated at DHF and HF levels of theory. It has been found that the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 8 publications
6
41
1
Order By: Relevance
“…One possible explanation for the high correlation is the inadequacy of the Clementi Hartree−Fock scattering factors, which incorporate neither correlation nor relativistic effects. These are probably significant for an element of such a high atomic number …”
Section: Methodsmentioning
confidence: 99%
“…One possible explanation for the high correlation is the inadequacy of the Clementi Hartree−Fock scattering factors, which incorporate neither correlation nor relativistic effects. These are probably significant for an element of such a high atomic number …”
Section: Methodsmentioning
confidence: 99%
“…A practical approach to this problem is placing positive charges outside a given radius around the ion (Watson, 1958;Schmidt & Weiss, 1979;Rez et al, 1994), but the resultant scattering curves differ significantly in the range sin/ < 0.4 Å À1 , depending on the size of the radius (Schmidt & Weiss, 1979). Previous studies (Wang et al, 1996;Macchi & Coppens, 2001) showed that the Dirac-Fock calculation yielded good solutions for O À and halides with no surrounding positive charges. Based on these studies, we carried out MCDF Plots of typical X-ray (upper row) and electron (lower row) scattering factors from the literature [e.g.…”
Section: Calculation Of Radial Wavefunctionsmentioning
confidence: 99%
“…Relativistic effects are known to be small for light atoms (e.g. Wang et al, 1996). Despite this, we included relativistic effects as most of the scattering factors in Colliex et al (2006) adopted the relativistic calculation, even for the atoms concerned in this study.…”
Section: Validation Of Scattering Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9,[17][18][19][20][21][22][23] The aim of the present study is a systematic investigation of relativistic effects on X-ray structure factors. While this topic has been studied for atomic form factors f (r * ) in the past, [24][25][26][27] there exists up to date no thorough study in this respect on structure factors F(r * ) based on a fully-relativistic reference. However, results from a previous study on relativistic effects on the topology of the electron density suggest, that especially for third row transition metal elements relativistic effects need to be taken into account in order to obtain accurate electron density distributions.…”
Section: Introductionmentioning
confidence: 99%